Making the French Pay: The Costs and Consequences of the Napoleonic Reparations - Eugene White (Rutgers University, Department of Economics, 1999)
Reparations as an instrument of international peace settlements were abandoned after the failure of Germany to pay its post World War I indemnity. However, reparations played a useful role in the construction of earlier peace treaties. This paper examines the payment of reparations by the French after the Napoleonic Wars. By most measures, these reparations were the largest ever fully paid; and they imposed a high cost on the economy in terms of lost output and consumption and diminished capital stock. The incentives to pay were appropriately set and payment permitted France to be accepted once again as an equal among the great powers.
Keywords: N13; 330; Reparations